2021
DOI: 10.1016/j.cegh.2021.100789
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hydatid cyst and related risk factors in humans referred to urban health centers of Zahedan city, southeast Iran

Abstract: Introduction: Cystic echinococcosis (CE) or hydatidosis is one of the most common diseases between humans and livestock that humans are considered as an accidental host. This disease has spread globally, especially in the Mediterranean region, including Iran. To the best of our knowledge, no specific research has been conducted to investigate the epidemiological status of this disease in Zahedan, Sistan and Baluchestan Province, Iran. Therefore, this study was performed to achieve that aim for the first time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
1
1
0
1
Order By: Relevance
“…The increase in cystic echinococcosis and T. solium cysticercosis seropositivity with age found by our study is consistent with that found by previous studies 31 , 17 . The most affected occupational groups for these zoonoses were housewives and farmers; a higher cystic echinococcosis seropositivity in housewives has been reported by other studies 32 . Likewise, the housing material, source of water for human consumption, consumption of unboiled water and defecating outdoors presented a difference in the seropositivity of human fascioliasis, where poverty and deficient sanitary conditions allow the perpetuation of this disease; this has been found by previous studies 8 , 26 , 33 .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The increase in cystic echinococcosis and T. solium cysticercosis seropositivity with age found by our study is consistent with that found by previous studies 31 , 17 . The most affected occupational groups for these zoonoses were housewives and farmers; a higher cystic echinococcosis seropositivity in housewives has been reported by other studies 32 . Likewise, the housing material, source of water for human consumption, consumption of unboiled water and defecating outdoors presented a difference in the seropositivity of human fascioliasis, where poverty and deficient sanitary conditions allow the perpetuation of this disease; this has been found by previous studies 8 , 26 , 33 .…”
Section: Discussionsupporting
confidence: 52%
“…El incremento de la seropositividad de equinococosis quística y cisticercosis de T. solium con la edad encontrado en nuestro estudio es consecuente con lo hallado en otros estudios 31 , 17 . Los grupos ocupacionales más afectados para estas zoonosis fueron las amas de casa y los agropecuarios, una mayor seropositividad de equinococosis quística en amas de casa ha sido reportado en otros estudios 32 . Asimismo, el material de la vivienda, fuente de agua para consumo humano, consumo de agua no hervida y deposición en campo libre presentaron una diferencia en la seropositividad de fascioliasis humana, donde la pobreza y las condiciones sanitarias deficientes permiten la perpetuación de esta enfermedad, lo que ha sido encontrado en otros estudios 8 , 26 , 33 .…”
Section: Discussionunclassified
“…This rate is in line with the studies conducted in other areas of Iran, including Yasuj (7.2-8.1%) in the Zagros Mountains of southwestern Iran, Khuzestan in the south (13.78%), Lorestan, a province of western Iran (15.4%), and Kermanshah (8.02%) in the western part of the country [12,[14][15][16][17]. Moreover, the seroprevalence rate of CE reported in this study is lower than those reported from the hot regions of Iran, including Isfahan (1.1%), Qom (1.6%), Markazi (3.46%), and Kashan (3.05%) in Central Iran and cold area including East Azerbaijan (1.28%), Hamedan (0.4%), and North Khorasan (3.96%) [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Following Table 1 , where the pooled prevalence across Asia was 0.0177, numerous studies found substantially higher rates of CE in certain regions, such as rural Mongolia (2.0% to 13.1%) [ 88 ], the Fars province of Southern Iran (8.73%) [ 89 ], and rural Zahedan, Iran (4%) [ 90 ]. The same holds true for South America, where the pooled prevalence was 0.0342, but higher prevalence rates were found in parts of Potos Department, Bolivia (4,3%) [ 91 , 92 ], and La Rioja Province, Argentina [ 93 ], emphasizing the need for more effective surveillance and control methods worldwide.…”
Section: Discussionmentioning
confidence: 99%